“Staring Down a Charging Bull”: Reconceptualizing Content and Disciplinary Literacy through Transmediation - Loerts, Terry (Language and Literacy / Langue et littératie, 2022)
This paper illustrates the findings from year three of a five-year research project where participants were asked to multimodally re-conceptualize their understandings about content and disciplinary literacy practices from a mandatory Bachelor of Education literacy course. Data collection includes transcribed interviews, professor feedback, in-class conversations with peers, multimodal artefacts, and participant notes taken during a gallery walk. Findings show that life experiences, transmediation processes, peer group sharing, and facility with modes and media contributed to deep understanding about multiliteracies practices, course content, and assessment techniques. Findings reveal that learning opportunities transcend disciplines, space, and time while enriching identity formation.